Analysis of the surface decoration of TiO2 grains using silver nanoparticles obtained by ultrasonochemical synthesis towards organic photovoltaics. (17th April 2018) - Michalska, Monika; Iwan, Agnieszka; Andrzejczuk, Mariusz; Roguska, Agata; Sikora, Andrzej; Boharewicz, Bartosz; Tazbir, Igor; Hreniak, Agnieszka; Popłoński, Sebastian; Korona, Krzysztof P.
Abstract : The wet ultrasonochemical method was used to obtained TiO2 / n -Ag nanoparticles for polymer solar cells. Abstract : In this article, we present a wet ultrasonochemical synthesis of nanocrystalline TiO2 powders in the anatase form in ethanol solution and their surface decoration using uniformly dispersed Ag metallic nanoparticles of about 4 nm at concentration of n = 0.5 to 2.5 wt% and those of 10–20 nm larger at a higher concentration than 1 wt%. The structure of the prepared composites was characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), atomic force microscopy (AFM), Raman and X-ray photoelectron spectroscopy (XPS). Optical properties were determined using UV-vis spectroscopy. Six polymer solar cells with modification by an TiO2 / n -Ag hole transporting layer were manufactured and studied under AM 1.5G-simulated solar illumination (100 mW cm −2 ). The best performance was obtained for a device with the ITO/(PEDOT:PSS):1.5%Ag in TiO2 /P3HT:PCBM/Al architectures. Under these conditions, a PCE of 2.07% with open circuit voltage V oc = 0.612 V, short circuit current density J sc = 5.94 mA cm −2, and fill factor FF = 0.57 was achieved. Additionally, devices were tested by electrochemical impedance spectroscopy under illumination and a well-fitted equivalent circuit was proposed. Finally, our idea of the linkage of TiO2 / n -Ag with PEDOT:PSS and P3HT in the constructed devices taking into account the amount of Ag in TiO2 was proposed.